Returning from study abroad and transitioning as a scholar: Stories of foreign PhD holders from Kazakhstan. - Kuzhabekova, A.; Sparks, J.; Temerbayeva, A. (Research in Comparative and International Education., 2019)
The article reports the results of an interview-based study exploring how international PhD holders re-integrate into the research environment in Kazakhstan. One of the main results consistent with prior studies is that returning scholars face poor access to international and domestic scholarly societies. Interaction with external peers is problematic due to insufficient funding available for conference participation. Lack of communication with the domestic scholarly community is related to its inaccessibility for junior researchers, as well as to its propensity to operate as an informal network of senior scholars controlling the protectionist distribution of funding and exerting influence on administrative and policy decision-making in academia. To counteract the informal networks, returning scholars get organized into alternative informal networks aimed at information exchange, mutual support and lobbying of interests. This transformative activity of junior scholars cannot be explained with the dominant structural theories in the existing research. An alternative Agency Theory interpretation is considered...
Keywords: readjustment; research capacity; returning scholars; study abroad